2021
DOI: 10.1177/10499091211042303
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Improve Palliative Care Delivery in Trauma Critical Illness

Abstract: Background: Despite recommendations to integrate palliative care (PC) into care for critically ill trauma patients, little is known about current PC practices in trauma care to inform opportunities for improvement. Objective: Describe patterns of PC delivery among a large, critically ill trauma cohort. Setting/Subjects: Retrospective cohort study of adult (≥18 years) trauma patients admitted to an intensive care unit (ICU) at an urban, level one trauma center in the United States from March 1, 2017 to March 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(87 reference statements)
0
2
0
3
Order By: Relevance
“…Ademais, um outro fator relevante é que a comunicação é um pilar e uma habilidade que deve ser aprimorada pelos profissionais como um todo, entre si e com o paciente e seus familiares, além de ser utilizada de maneira clara e concisa, evitando interpretações equivocadas, sendo, portanto, útil a implementação de práticas de conversação (HAINES et al, 2022;PUN et al, 2022). Para mais, o paciente e sua autonomia devem ser incluídos no âmago das discussões do plano de cuidados a fim de que seja obtido o melhor cenário possível para tal (NAUCK; JASPERS, 2021).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ademais, um outro fator relevante é que a comunicação é um pilar e uma habilidade que deve ser aprimorada pelos profissionais como um todo, entre si e com o paciente e seus familiares, além de ser utilizada de maneira clara e concisa, evitando interpretações equivocadas, sendo, portanto, útil a implementação de práticas de conversação (HAINES et al, 2022;PUN et al, 2022). Para mais, o paciente e sua autonomia devem ser incluídos no âmago das discussões do plano de cuidados a fim de que seja obtido o melhor cenário possível para tal (NAUCK; JASPERS, 2021).…”
Section: Discussionunclassified
“…Foram realizadas buscas sistemáticas nas bases de dados do PUBMED com os seguintes descritores de pesquisa e operadores booleanos: ''integrative palliative care'' AND ''emergencies'' AND ''communication'' NOT ''pediatrics'', de acordo Um dos temas abordados em destaque é o despreparo dos profissionais que compõem uma emergência ao conhecimento dos CP (KAMPHAUSEN et al, 2019), haja vista que, no cenário ideal, os médicos estão habituados a oferecer diagnóstico e resolução de alta qualidade nas doenças não relacionadas à malignidade (ALQAHTANI; MITCHELL, 2019, ROWE et al, 2021. Ademais, somado a isso, há o fato de que médicos do departamento de emergência têm profundo compromisso com os pacientes em oferecer cuidados e garantir resultados ideais, ou seja, a vida (HAINES et al, 2022). Nesse contexto, os autores fomentam a concepção da falta de conhecimento sobre CP (BHAT et al, 2023;VOUMARD et al, 2018).…”
Section: Métodosunclassified
See 1 more Smart Citation
“…Interestingly, they also found of all those who received hospice or PC services, surgical patients lived longer than medical patients (median: 26 days vs 23 days; p<0.001). 25 Conversely, a 2022 single-center study by Haines et al found that 6.2% of trauma patients received orders for PC and 1.1% were discharged to hospice, 26 suggesting that at a minimum, the general trauma population experiences different utilization rates of hospice or PC than Veterans.…”
Section: Open Accessmentioning
confidence: 99%
“…19 Though palliative/ end of life care plays a significant role in relieving health-related suffering, 20 its integration in intensive care units (ICUs) is faced with varied challenges such as lack of policies/ guidelines and negative attitudes/ perceptions of healthcare staff. 21 In fact, evidence for PC in these traditionally non-PC setting is even sparser 22 though a few small observational studies suggest trauma patients admitted to the ICU may benefit from palliative care. [23][24][25] So far, three models to facilitate the integration of palliative/ end of life care in the ICU have been identified in existing literature: integrative, consultative, and combined or mixed models.…”
Section: Introductionmentioning
confidence: 99%